Antibacterial potential of celery (Apium graveolens L.) extract gel against Staphylococcus aureus - Martinus Ezra Sunarno; Anita Lidesna Shinta Amat; Arley Sadra Telussa; Prisca Deviani Pakan (Acta Biochimica Indonesiana)
Background: Staphylococcus aureus can cause furuncles or boils, painful nodules on the skin. Conventional topical therapies often lead to side effects such as contact dermatitis and pruritus, compounded by the increasing problem of antibiotic resistance. Natural ingredients like celery (Apium graveolens L.) offer promising alternatives due to their antibacterial properties and gentler effects.